Left persistent superior vena cava with large coronary sinus: A case report - Doğan, Emrah; Mouline Doğan, Marwa; Gül, Süha; Çullu, Neşat (Journal of Surgery and Medicine, 2019)
Persistent left superior vena cava (LPSVC) is a rare and important congenital venous anomaly. It is caused by a defect in the closure of the left anterior cardinal vein during cardiac development. The LPSVC drains into the right atrium via the coronary sinus (CS) in 90% of cases, connects to the left atrium in 10 % of them. When cardiac anomalies are present, LPSVC is usually linked directly to left atrium. Thus, LPSVC which drains in the CS is generally isolated and asymptomatic. In our case, patient presented a heavy respiratory symptomatology without any diagnosis since all of the respiratory tests were normal. After realization of a computed tomography (CT), LPSVC had been discovered inducing a huge dilatation of CS, which its diameter was three times more than reported in literature and without any associated congenital heart disease. LPSVC seems to be a complex anatomic variation with different clinic and anatomic shapes. CS dilatation can be found in association with LPSVC in CT. As a result, it is important to use non-invasive cardiovascular examinations to make an optimal diagnosis of congenital cardiovascular variations and in order to avoid further interventional complications.